Keragaman Spesies Ikan Tuna di Pasar Ikan Kedonganan Bali dengan Analisis Sekuen Kontrol Daerah Mitokondria DNA (SPECIES DIVERSITY OF TUNA FISH USING MITOCHONDRIAL DNA CONTROL REGION SEQUENCE ANALYSIS AT KEDONGANAN FISH MARKET) - Hariyanto, Daud Steven Triyomi; Mahardika, I Gusti Ngurah Kade; Wandia, I Nengah (Jurnal Veteriner; Vol 16 No 3 (2015), 2015)
Tuna is an export commodity which has very high economic value. However, some tuna speciesare threatened with extinction. The purpose of this study was to identify the tuna species that aresold in Kedonganan Fish Market. The research method was polymerase chain reaction technique(PCR) using the marker sequence mitochondrial DNA control region. Samples were obtained fromthe Fish Market tuna Kedonganan, Kuta, Badung, Bali. The total number of samples are 28specimens. Sequence from each sample was obtained through sequencing techniques. Sequencesobtained were run in BLAST (Basic Local Alignment Search Tool) and subsequently analyzed withMEGA 5 for species confirmation. Three species of tuna that are identified in the Kedonganan FishMarket is: Thunnus albacares, T. obesus, and Katsuwonus pelamis. All three species have highgenetic variation HD = 1. This study needed to be continued with more number of samples todetermine the species of tuna sold in Kedonganan Fish Market.
Keywords: tuna fish, mitochondrial DNA control region, Kedonganan